2016
DOI: 10.1590/1678-4162-8217
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological presentation of squamous metaplasia of the rete ovarii in a Zebu cow

Abstract: Squamous metaplasia of rete ovarii is characterized by replacement of the normal cuboidal epithelium of rete ovarii by a keratinized stratified scamous epithelium, leading to accumulation of keratinized material within the tubules and cystic dilatation of rete ovarii. The present study decribes a case of scamous metaplasia of rete ovarii in a 10 year old Zebu cow, including clinical, surgical, ultrasonographic, histopathological and hormonal findings. At first ultrasound examination the cow had lightly asymmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
1
0
1
Order By: Relevance
“…Histopathological findings in this case were quite similar to previously reported cases of squamous metaplasia of the rete ovarii (Santos et al, 2012;Borges et al, 2016). Epidemiologic data on prevalence and predisposing factors for metaplasia of the rete ovarii is missing, but this case along with the previously reported cases all affecting Zebu cows (Santos et al, 2012;Borges et al, 2016), support the notion that Zebu or crossbreed Zebu cows may be predisposed to the development of this lesion.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Histopathological findings in this case were quite similar to previously reported cases of squamous metaplasia of the rete ovarii (Santos et al, 2012;Borges et al, 2016). Epidemiologic data on prevalence and predisposing factors for metaplasia of the rete ovarii is missing, but this case along with the previously reported cases all affecting Zebu cows (Santos et al, 2012;Borges et al, 2016), support the notion that Zebu or crossbreed Zebu cows may be predisposed to the development of this lesion.…”
Section: Discussionsupporting
confidence: 88%
“…In spite of cystic changes occupying extensive areas in both ovaries, Santos et al (2012) confirmed that the cow maintained ovarian cyclic activity, as evidenced by a mature and apparently functional corpus luteum and ovarian follicles in the ovary affected by the lesion. More recently, a second report by Borges et al (2016) confirmed ovarian luteal activity with clinical, gynecological and endocrinological assessment in a Zebu cow, which confirmed that the cow was able to maintain ovarian follicular growth and ovulation followed by the development of a functional corpus luteum, as confirmed by normal blood levels of progesterone assessed by chemiluminescent enzyme immunoassay. In this case report we diagnosed ovarian cystic changes, secondary to squamous metaplasia of the rete ovarii, associated with follicles, dark brown older corpora albicantia indicating previous ovulations, a mature corpus luteum, associated with early pregnancy.…”
Section: Discussionmentioning
confidence: 78%
“…[9] e Borges et al [2] relataram que os cistos dermoides podem confundir-se com metaplasia escamosa de rete ovarii devido à similaridade de algumas características, como a presença do epitélio estratificado queratinizado e a presença de material queratínico no interior dos cistos. Contudo, na metaplasia escamosa de rete ovarii há presença de epitélio cuboidal, simples ou duplo e no cisto dermoide o epitélio de revestimento é estratificado contendo debris queratínicos no lúmen.…”
Section: Discussionunclassified